Azide-functionalized Hollow Silica Nanospheres for Removal of Antibiotics - Gao, J.; Chen, J.; Li, X.; Wang, M.; Zhang, X.; Tan, F.; Xu, S.; Liu, Jian (Academic Press, 2015)
Antibiotics, which are hardly removed from polluted water by conventional water-treatment technologies, adsorption has been deemed as one of the efficient and promising method to resolve the problems of antibiotics pollution. Herein, we reported a synthesis of filtration separable hollow nanostructured silicas (HNSs) with efficient click functionalization property for antibiotics adsorption. The clickable HNSs were synthesized by the co-condensation and assembling of tetramethoxysilane (TMOS) and 3-azidopropyltrimethoxysilane (AzPTMS) around F127 single micelle template. Alkynyl compounds such as phenylacetylene (Ph), propargyl alcohol (PA), 1-heptyne (Hep), and 2-butyne-1,4-diol (BD) have been linked to the materials through click reaction with high efficiency. Antibiotic adsorption results reveal that functional groups play an important role in adsorption properties of adsorbents and phenyl was found to be the optimal functional group due to the π–π stacking effect. Excellent adsorption capacity and recyclability indicate that the clickable hollow nanostructured silicas exhibit potential application for antibiotics removal.